Efecto del programa Juego de las Operaciones Básicas de Adición y Sustracción (JOBAS) en el nivel del cálculo mental de las operaciones básicas de los alumnos de primer grado de educación primaria de la institución educativa reino de Suecia - Chumbes Yataco, Jeanette Carmen (2010)
The research focuses its objectives on the effectiveness of the application of the game program of the basic operations of addition and subtraction (JOBAS) in the mental arithmetic levelof the basic operations of first grade primary school students of the public school "Reino de Suecia" in "Santiago de Surco" district.